The Genetic Landscape of Children Born Small for Gestational Age with Persistent Short Stature - Toni, Ledjona; Plachy, Lukas; Dusatkova, Petra; Amaratunga, Shenali Anne; Elblova, Lenka; Sumnik, Zdenek; Kolouskova, Stanislava; Snajderova, Marta; Obermannova, Barbora; Pruhova, Stepanka; Lebl, Jan (Hormone research in paediatrics, 2024)
INTRODUCTION: Among children born small for gestational age, 10-15% fail to catch up and remain short (SGA-SS). The underlying mechanisms are mostly unknown. We aimed to decipher genetic aetiologies of SGA-SS within a large single-centre cohort. METHODS: Out of 820 patients treated with growth hormone (GH), 256 were classified as SGA-SS (birth length and/or birth weight <-2 SD for gestational age and life-minimum height <-2.5 SD). Those with the DNA triplet available (child and both parents) were included in the study (176/256). Targeted testing (karyotype/FISH/MLPA/specific Sanger sequencing) was performed if a specific genetic disorder was clinically suggestive. All remaining patients underwent MS-MLPA to identify Silver-Russell syndrome, and those with unknown genetic aetiology were subsequently examined using whole-exome sequencing or targeted panel of 398 growth-related genes. Genetic variants were classified using ACMG guidelines. RESULTS: The genetic aetiology was elucidated in 74/176 (42%) children. Of these, 12/74 (16%) had pathogenic or likely pathogenic (P/LP) gene variants affecting pituitary development (LHX4, OTX2, PROKR2, PTCH1, POU1F1), the GH-IGF-1 or IGF-2 axis (GHSR, IGFALS, IGF1R, STAT3, HMGA2), 2/74 (3%) the thyroid axis (TRHR, THRA), 17/74 (23%) the cartilaginous matrix (ACAN, various collagens, FLNB, MATN3), and 7/74 (9%) the paracrine chondrocyte regulation (FGFR3, FGFR2, NPR2). In 12/74 (16%), we revealed P/LP affecting fundamental intracellular/intranuclear processes (CDC42, KMT2D, LMNA, NSD1, PTPN11, SRCAP, SON, SOS1, SOX9, TLK2). SHOX deficiency was found in 7/74 (9%), Silver-Russell syndrome in 12/74 (16%) (11p15, UPD7), and miscellaneous chromosomal aberrations in 5/74 (7%) children. CONCLUSIONS: The high diagnostic yield sheds a new light on the genetic landscape of SGA-SS, with a central role for the growth plate with substantial contributions from the GH-IGF-1 and thyroid axes and intracellular regulation and signalling.
Keywords: Short Stature Homeobox Protein; Dwarfism; hypotrofický novorozenec; gestační stáří; Silver-Russell Syndrome; Child; Insulin-Like Growth Factor I; Gestational Age; dítě; Silverův-Russellův syndrom; protein SHOX; Body Height; Growth Disorders; tělesná výška; nanismus; poruchy růstu; novorozenec; insulinu podobný růstový faktor I; lidé; Humans; Infant, Newborn; Human Growth Hormone; Infant, Small for Gestational Age; lidský růstový hormon